Genomic analysis of \(Aeromonas hydrophila\) bacteriophages isolated in striped catfish farms in the Mekong delta, Vietnam - Vinh, Tu Quang; Nhan, Nguyen Le Hoai; Xuan, Tran Thi Thanh; Nga, Le Phi; Hoang, Hoang Anh (Academia Journal of Biology, 2021)
Striped catfish or Vietnamese catfish mainly contributes to national aquaculture exports. However, bacterial diseases result in the decrease of striped catfish production efficiency and the most popular disease is hemorrhagic septicemia caused by Aeromonas hydrophila. Bacteriophages or bacterial viruses have been investigated as alternative biological agents to control pathogenic bacterial infections in aquaculture for many decades. A few genomes of striped catfish A. hydrophila bacteriophages have been analyzed, although many genomes of A. hydrophila bacteriophages in other fish have been investigated. In this study, the whole genome sequences of three new A. hydrophila bacteriophages such as PVN03, PVN04 and PVN05 were described. The morphological analysis by transmission electron microscopy indicated that these phages belonged to Myoviridae family. The genome sizes of the phages PVN03, PVN04 and PVN05 were 50,725 bp, 51,721 bp and 51,884 bp, respectively. PVN03 had 64 open reading frames (ORFs), while PVN04 and PVN05 had 65 ORFs and 66 ORFs, respectively. No tRNAs, rRNAs or sRNAs, antibiotic resistance genes, virulence factors, toxin genes and integrase genes were detected in three phage genomes. ANI analysis tool showed that Aeromonas hydrophila phages isolated in Vietnam formed a distinct group having a very low similarity with other Aeromonas hydrophila phages available on the database. In addition, phylogenetic tree analysis indicated that these phages formed a new genus in the Myrovidae family.